The response of cecal microbiota to inflammatory state induced by Salmonella enterica serovar Enteritidis - Hu, Geng; Liu, Liying; Miao, Xiuxiu; Zhao, Yanan; Peng, Yanan; Liu, Lewen; Li, Xianyao (Frontiers in Microbiology, 2022)
By combining the experiments of reciprocal crosses of chicken infected with Salmonella enterica serovar Enteritidis (S. Enteritidis), we focused on the common response of cecal microbiota to an inflammatory state in respect of transcriptome and microbiome. The inoculation of S. Enteritidis improved the microbial diversity and promoted the microbiota evolution in our infection model. Correlation analysis between bacteria and inflammation-related genes showed that some intestinal microorganisms were “inflammophile” and thrived in an inflamed environment. The global function of cecal microbiome was to maintain the homeostasis likely by the up-regulation of microbial metabolism pathway in bacitracin, putrescine, and flavonoids production, although the bacitracin may affect the symbiotic bacteria Enterococcus. The action of S. Enteritidis had close relationships with multiple inflammation-related genes, including the genes PTAFR, LY96, and ACOD1 which proteins are related to the binding and tolerance of LPS, and the genes IL-18, IL-18R1 and IL-18RAP which products can form a functional complex and transmit IL-18 pro-inflammatory signal. Additionally, the infection of S. Enteritidis aroused the transcription of EXFABP, which protein has a potential to sequestrate the siderophore and might cause the decline of Escherichia-Shigella and Enterococcus. S. Enteritidis can escape from the sequestrating through the salmochelin, another kind of siderophore which can’t be recognized by EXFABP. Probably by this way, S. Enteritidis competed with the symbiotic bacteria and edged out the niches. Our research can help to understand the interplay between host, pathogen, and symbiotic bacteria.